Economics of disability: An empirical study of disability and employment in the Bangladesh district of Chuadanga - Chowdhury, Jahan; Foley, Dermot (Disability Studies Quarterly, 2006)
Depending on a range of social and economic factors, a person who is labeled with a disability and the household where s/he resides face transitions in their financial circumstances- changes that can topple their lives, depriving them of basic human necessities. In this study we examine these circumstances for households in the Chuadanga district in Bangladesh. The impact of being labeled with a disability varies across households and individuals. One objective of this study is to determine which groups are more adversely affected and why. The authors analyze transitions in the lifestyles of other household members, e.g., spouse or dependent parents, owing to labeling of a disability, in order to present the overall change in economic activity of the household. Emphasis is placed on exclusion from full-time paid employment, the burdens of complete caring responsibilities and related opportunity costs, and how compromises are made between employment and care responsibilities. Overall, the paper broadens the analysis from poverty and employment to other aspects of life, including economic responsibility, social participatory preoccupations or coping strategies influenced by being labeled with a disability. Based on this research, the authors find that even if the household is able to retain its previous earnings, increased expenditure resulting from the new situation reduces net earnings to an enormous extent. The labelling of a family member with a disability often hinders the economic well-being of the household. Therefore, the structure of the household should be of great concern when analyzing the impact of disability. All members of an affected household experience a change in their daily activities, be they other earners or dependents, like children, who forego education and may have to contribute to income as well. Having a spouse in these situations can serve as a blessing, as income-earning responsibilities can be shared, but the abrupt changes in quality of life often yield tension between the couple, arising from frustration and helplessness. Often, transitions following the onset of impairment of the main earner being labeled with a disability, result in intense poverty.